Study of patients with diminished ovarian reserve and our approach to their treatment: retrospective analytic study - Mitra, Sujoy; Srinivas, Sangisapu; Pathak, Baidyanath; Aiyyer, Uttara; Patil, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Diminished ovarian reserve (DOR) is a perplexing entity. For the physician, optimisation of all aspects of management is needed to fruitfully utilise the available pool of gametes and time. Methods: In this multicentric retrospective analytic study, we re-evaluated all cases of DOR. All aspects of management were critically assessed. Results: We saw that idiopathic DOR was the most common etiology. AMH titres are reflection of oocyte yield. Stop agonist-antagonist and micro dose flare gives a higher oocyte yield. More number of good quality blastocyst was available in antagonist cycles. Growth hormone as adjuvant is helpful in DOR cases. Conclusions: DOR needs special care and urgency in treatment. Appropriate selection of protocol and adjuvants to treatment gives adequate pregnancy rate.